Continuous Service Quality Improvement and Change Management for Children and Young People with Autism and Their Families: A Model for Change. Issue 3 (2nd July 2016) - Kennedy, R.; Binns, F.; Brammer, A.; Grant, J.; Bowen, J.; Morgan, R.
ABSTRACT: A case study approach was used that included data collection from a wide range of sources, e.g., a stakeholder conference, audit, questionnaires, and evaluative feedback from carers, families, staff, and Autism Champions. Integrated pathways for patient care improvement were developed. Families and carers were involved in raising awareness of the needs of children with autism and policy development to meet these needs. Increased involvement from interdisciplinary working strengthened the work of the Recognising Autism Management Programme (RAMP) and improved patient care outcomes. The interventions undertaken by the RAMP resulted in improved patient /carer satisfaction, the reduction of challenging behaviour, complaints, and treatment refusal. The Autism Champions played a significant role in signposting resources and the cascading of education and practice development. All children and young people (0–25 years) on the Autism Spectrum and their families benefit from safe, individualised, high quality care in a supportive environment. Education of staff and families and targeted actions in adapting attitudes and behaviours in communication and care management will result in positive experiences for staff, children and families and financial benefit to the NHS Trust by reducing cancellation of appointments and operating theatre slots.